2012
DOI: 10.1590/s1517-70762012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformação da cinza da casca de arroz em nanopartículas de sílica mediante Fusarium oxysporum

Abstract: RESUMONeste estudo avaliou-se uma rota biológica à temperatura ambiente para a biotransformação da cinza da casca de arroz em nanopartículas de sílica empregando o fungo Fusarium oxysporum. Foram realizados ensaios e monitorou-se a produção de biomassa fúngica, pH e concentração de sílica solúvel em meio de cultura contendo cinza durante 270 h a uma temperatura de 25°C, com uma concentração inicial de biomassa de 0,3 g/L (base úmida) in situ. A cinza antes e após o tratamento foi analisada por espectroscopia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…This biotechnology has also been linked to genetic and biochemical issues, evaluating the alterations that secondary metabolites, dispersed in the environment, It must be mentioned that concomitant biotransformation has also been addressed at the intersection of activities in the food industry and industrial innovations. Used in modern chemistry as a tool capable of signaling biological routes for obtaining the most varied products, such as nanoparticles from waste from the agroindustry, reducing their quantities and promoting the obtaining of value-added products (PINEDA et al, 2012), or obtaining secondary metabolites with potential for medicine, agriculture or industry (VALENTE et al, 2013).…”
Section: General Aspects Of Microbial Biotransformation Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…This biotechnology has also been linked to genetic and biochemical issues, evaluating the alterations that secondary metabolites, dispersed in the environment, It must be mentioned that concomitant biotransformation has also been addressed at the intersection of activities in the food industry and industrial innovations. Used in modern chemistry as a tool capable of signaling biological routes for obtaining the most varied products, such as nanoparticles from waste from the agroindustry, reducing their quantities and promoting the obtaining of value-added products (PINEDA et al, 2012), or obtaining secondary metabolites with potential for medicine, agriculture or industry (VALENTE et al, 2013).…”
Section: General Aspects Of Microbial Biotransformation Approachesmentioning
confidence: 99%
“…Microbial biotransformation can be understood as a biotechnology based on the oxidation of organic compounds through biological routes, from micro-organisms or enzymes secreted by them (PINEDA et al, 2012;SILVA et al, 2012;OLIVEIRA et al, 2015). Demonstrating to be efficient in a wide range of research areas, according to what has been developed and reported in scientific productions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na Figura 7 observa-se o difratograma da amostra I, identificando a parte amorfa na cinza da casca de trigo e sílica, apresentando um halo amorfo nos ângulos de difração (2θ) de 18º a 38º e contendo dois picos dentro deste halo amorfo, indicando cristalização. Esses picos cristalinos correspondem ao polimorfo cristalino denominado de cristobalita, com índice de Muller (101) referente ao pico principal [33,34]. Segundo ARAS e KRISTALY [35] a alta concentração de sílica sempre corresponde a alta concentração de quartzo, entretanto em função da diversa quantidade de outros elementos presentes na amostra como identificados por EDS e a elevada temperatura de aquecimento, pode ter sido um fator importante para conversão da estrutura de quartzo para cristobalita [33].…”
Section: Difração De Raios X (Drx)unclassified
“…According to Pineda et al (2012), the peaks related to silica are comprised between the wave lengths of 500 to 1250 cm -1 and in the range of 540 to 800 cm -1 , associated with the balance and flexion mode of the compound containing silica (SiO2). All the samples showed intense absorption between 950 and 1150 cm -1 ( Figure 5), attributed to the vibrations of the stretching of Si-O-Si asymmetrical molecules (CHAVES et al, 2009;FERNANDES et al, 2018;MANIQUE et al, 2012).…”
Section: Segregation and Characterization Of The Adsorbent Materialsmentioning
confidence: 99%